Multilevel omics for the discovery of biomarkers and therapeutic targets for stroke - Montaner, Joan; Ramiro, Laura; Simats, Alba; Tiedt, Steffen; Makris, Konstantinos; Jickling, Glen C; Debette, Stephanie; Sanchez, Jean-Charles; Bustamante, Alejandro (Nature reviews. Neurology, 2020)
Despite many years of research, no biomarkers for stroke are available to use in clinical practice. Progress in high-throughput technologies has provided new opportunities to understand the pathophysiology of this complex disease, and these studies have generated large amounts of data and information at different molecular levels. The integration of these multi-omics data means that thousands of proteins (proteomics), genes (genomics), RNAs (transcriptomics) and metabolites (metabolomics) can be studied simultaneously, revealing interaction networks between the molecular levels. Integrated analysis of multi-omics data will provide useful insight into stroke pathogenesis, identification of therapeutic targets and biomarker discovery. In this Review, we detail current knowledge on the pathology of stroke and the current status of biomarker research in stroke. We summarize how proteomics, metabolomics, transcriptomics and genomics are all contributing to the identification of new candidate biomarkers that could be developed and used in clinical stroke management.